Disaster-related social behavior in the Philippines - Nelson, Gloria Luz M. (UP Los Baños Journal, 2008)
This paper reviewed articles on the social behavior of Filipinos during and after the natural disaster. In the family, household and the community contexts. The response of the government and non-government organizations was likewise reviewed to complete the picture on the coping behavior of Filipinos amid natural disasters. Filipinos have employed self-help strategies starting from the family members to the community leaders to bring back normalcy in their living arrangements and in their farm activities. Government and non-government organizations focused mainly on the rehabilitation aspect through provisions of relief goods and resettlement areas. To provide effective management of disaster, preparedness coupled with mitigation should be given due attention for a more proactive rather than reactive response.